Sex differences in glutamate transmission and plasticity in reward related regions - Kniffin, Alyssa R.; Briand, Lisa A. (Frontiers in Behavioral Neuroscience, 2024)
Disruptions in glutamate homeostasis within the mesolimbic reward circuitry may play a role in the pathophysiology of various reward related disorders such as major depressive disorders, anxiety, and substance use disorders. Clear sex differences have emerged in the rates and symptom severity of these disorders which may result from differing underlying mechanisms of glutamatergic signaling. Indeed, preclinical models have begun to uncover baseline sex differences throughout the brain in glutamate transmission and synaptic plasticity. Glutamatergic synaptic strength can be assessed by looking at morphological features of glutamatergic neurons including spine size, spine density, and dendritic branching. Likewise, electrophysiology studies evaluate properties of glutamatergic neurons to provide information of their functional capacity. In combination with measures of glutamatergic transmission, synaptic plasticity can be evaluated using protocols that induce long-term potentiation or long-term depression. This review will consider preclinical rodent literature directly comparing glutamatergic transmission and plasticity in reward related regions of males and females. Additionally, we will suggest which regions are exhibiting evidence for sexually dimorphic mechanisms, convergent mechanisms, or no sex differences in glutamatergic transmission and plasticity and highlight gaps in the literature for future investigation.